Using Hooke's Law, the spring would stretch a total of 19.5 cm when 13 washers are placed on it.
To find out how much a spring would elongate when the number of washers is increased, we use Hooke's Law, which describes linear elasticity.
Since it is given that 3 washers cause the spring to stretch 4.5 cm, we can assume that each washer causes an equal amount of stretch under this elastic limit. Therefore, the amount of stretch per washer is 4.5 cm divided by 3, which is 1.5 cm per washer.
If you hang 13 washers on the spring, the total stretch can be calculated by multiplying the amount of stretch per washer with the total number of washers:
Stretch per washer × Number of washers = Total stretch
1.5 cm/washer × 13 washers = 19.5 cm.
So, with 13 washers, the spring would stretch a total of 19.5 cm.
Solve the inequality and graph its solution: x - 7>-20
A x>-13
-12
6
0
6
12
18
24
30
-30 -24 -18
B. x>-13
-6
0
6
12
18
24
30
-30 -24 -18 -12
cx<-27
6
0
6
12
18
24
30
-3024 -18 -12
X<-27
D.
+
+ +
--3026 -18
1
-12
6
0
6
12
18
24
30
The inequality x - 7 > -20 is solved by adding 7 to both sides, resulting in x > -13. The graph of this inequality has an open circle at -13 with shading to the right.
To solve the inequality x - 7 > -20, you want to isolate the variable x on one side. You can do this by adding 7 to both sides of the inequality:
x - 7 + 7 > -20 + 7
x > -13
So, the solution to the inequality is x > -13. To graph this solution on a number line, you would draw an open circle at -13 and shade to the right, indicating that x can be any value greater than -13 but not including -13 itself.
A particular company's net sales, in billions, from 2008 to 2018 can be modeled by the expression t2 + 10t + 68, where t is the number of years since the end of 2008. What does the constant term of the expression represent in terms of the context?
The company earned 68 billion dollars from 2008 to 2018.
The company earned 68 billion dollars in 2008.
The company earned 10 billion dollars from 2008 to 2018.
The company earned 10 billion dollars in 2008.
Answer:
The company earned 68 billion dollars in the year 2008..
Step-by-step explanation:
This is because the time t is the number of years since the END of 2008. The time t = 0 at the end of 2008, so the earnings = 0^2 + 10(0) + 68 = 68 billion.
Answer:
option B
Step-by-step explanation:
A particular company's net sales is modeled by the expression (t² + 10t + 68)
Where t represents number of years since the end of year 2008.
In this expression 68 is the constant term which represents the earning of the company before 2008. or in year 2008.
The company earned 68 billion dollars in 2008.
Therefore, option B is the answer.
Write the expression 3x24 + 4x12 + 7 in quadratic form.
Answer:
3 m^2 + 4m +7
Step-by-step explanation:
3x^24 + 4x^12 + 7
Let m =x^12
m^2 = x^12 ^2 = x^24
Substitute this into the first equation
3 m^2 + 4m +7
roll a single die what is the probablity of rolling a number lesss than 7
Answer:
Does it say a standard 6 sided die because if so then it would be 6/6 probability because the number can only go up to 6 an so there is no probability of getting anything more then 6
Step-by-step explanation:
what is the square root of 4/9?
please explain the steps.
Thank you!
Answer:
I just know it is 0.222222222222
Step-by-step explanation:
Answer:
± [tex]\frac{2}{3}[/tex]
Step-by-step explanation:
Given
[tex]\sqrt{\frac{4}{9} }[/tex]
= [tex]\frac{\sqrt{4} }{\sqrt{9} }[/tex] = ± [tex]\frac{2}{3}[/tex]
Which equation shows an example of the associative property of addition?
(-7 + 1) + 71 = -7+ (i + 78)
(-7 + 1) + 7i = 71 +(-7i+1)
71% (-77 + 1) = (71-71) + (7ix)
(-71 + 1) + 0 = (-71 +1)
D
(-71+1) + 0 = (-71+1)
This is because the whole equation involves addition thus it is an example of associative property of addition
Answer:
(-71 + 1) + 0 = (-71 +1)
Step-by-step explanation:
Given 3 numbers: a,b,c
Associative property of addition: (a + b) + c = a + (b + c)
On this case: a= -71
b = 1
c = 0
(a + b) + c = (-71 + 1) + 0 = -70 + 0 = -70
(-71 + (1 + 0)) = (-71 + 1) = -70
Both the sums are equal to -70 and hence the associative property of addition for the three numbers a= -71, b = 1, c= 0 holds.
All the other options in the question contain a reference to variable i and does not have the same three values a,b,c on both sides of the equality. So they do not represent the associative property.
Can someone please help me out here ?
Answer:
4
Step-by-step explanation:
The median is the middle, since the amount of data is an even number we need to add up the third number and fourth number. These are 3 and 5 respectively. Adding these up gives up 8. Dividing this by 2 is 4.
Find a, b, and c.
A. a = 12,b = 6 root 3,c = 3 root 6
B. a = 12, B = 12 root 2, c = 3 root 6
C. a = 6 root 3, b = 12 root 3, C = 6 root 2
D. a = 6 root 3, b = 12 root 3,c= 6 root 2
Answer:
Option C.
[tex]a=6\sqrt{3}[/tex]
[tex]b=12[/tex]
[tex]c=6\sqrt{2}[/tex]
Step-by-step explanation:
step 1
Find the value of a
we know that
[tex]tan(60\°)=a/6[/tex]
Remember that
[tex]tan(60\°)=\sqrt{3}[/tex]
so
[tex]a/6=\sqrt{3}[/tex]
[tex]a=6\sqrt{3}[/tex]
step 2
Find the value of b
we know that
[tex]cos(60\°)=6/b[/tex]
Remember that
[tex]cos(60\°)=1/2[/tex]
so
[tex]6/b=1/2[/tex]
[tex]b=12[/tex]
step 3
Find the value of c
we know that
[tex]cos(45\°)=c/b[/tex]
[tex]cos(45\°)=c/12[/tex]
Remember that
[tex]cos(45\°)=\sqrt{2}/2[/tex]
[tex]c/12=\sqrt{2}/2[/tex]
[tex]c=6\sqrt{2}[/tex]
Answer:
C.
Step-by-step explanation:
Which graph shows a rate of change of 1/2
between -4 and 0 on the x-axis?
Answer:
Step-by-step explanation:
its the first one in edge
The graph which shows a rate of change of 1/2 is the linear graph shown in the image attached below.
What is the Rate of Change?Rate of change = change in y / change in x.
The two points between -4 and 0 on the x-axis as shown in the diagram attached are, (-4, 1) and (0, 3). It is also a linear graph.
Rate of change = (3 - 1)/(0 -(-4)) = 2/4 = 1/2
The graph that shows a rate of change is the linear graph attached below.
Learn more about the rate of change on:
https://brainly.com/question/25184007
#SPJ5
What are the solutions to the equation 4x2+3x=24-x
Answer:
x=2 x=-3
Step-by-step explanation:
4x2+3x=24-x
Subtract 24 from each side
4x^2 +3x -24 = 24-24 -x
4x^2 +3x -24 = -x
Add x to each side
4x^2 +3x+x -24 = -x+x
4x^2 +4x -24 = 0
Factor out a 4
4(x^2 +x -6) = 0
Divide by 4
x^2 +x -6 =0
Factor
What 2 numbers multiply to -6 and add to 1
-2*3 = -6
-2+3 =1
(x-2) (x+3) =0
Using the zero product property
x-2 =0 x+3 =0
x-2+2=0+2 x+3-3=0-3
x=2 x=-3
Answer:x=-3 , x = 2
Step-by-step explanation:
First move the expression ( 24-x) to the left.
This gives us 4x^2+3x+24-x.
Collect the like terms which gives us 4x^2+4x+24
4x^2+4x-24 = 0. Divide both sides by 4.
x^2 + x-6 = 0
Factorise the expression so you get (x+3)(x-2)=0
Solve the equations x+3 = 0 and x-2=0
The final solutions are x=-3 and x=2.
How many ounces of trial mix are in a bag that weighs.908 kilograms?
Answer:
32028.8 ounces
Step-by-step explanation:
We are given that there are 908 kilograms of of trial mix are in a bag and we are to find the number of ounces of the same amout of mix in the bag.
For that, we will use the ratio method.
We know that, 1 kg = 35.274, so:
[tex] \frac { 1 k g }{908kg} =\frac{35.274 oz}{x}[/tex]
[tex]x=32028.8[/tex]
Therefore, there are 32028.8 ounces of mix in the bag.
Final answer:
To find the amount of trail mix in ounces from 0.908 kilograms, convert the weight to grams and then to ounces using the conversion of 1 oz = 28.35 g, resulting in approximately 32.012 ounces of trail mix.
Explanation:
To convert the weight of the trail mix from kilograms to ounces, we need to use the conversion factor: 1 oz is produced by a mass of 28.35 g. First, convert the kilograms to grams by multiplying by 1000, because there are 1000 grams in a kilogram. Then, once we have the weight in grams, we can convert grams to ounces using the provided conversion rate.
Here's the calculation step by step:
Convert kilograms to grams: 0.908 kg × 1000 = 908 grams.
Convert grams to ounces: 908 g ÷ 28.35 g/oz = 32.012 ounces (rounded to three decimal places).
Thus, a bag that weighs 0.908 kilograms contains approximately 32.012 ounces of trail mix.
Consider the two exponential equations shown. Identify the attributes for each equation to complete the table.
Answer:
[tex] y = 2 5 0 ( 0 . 8 9 ) ^ x [/tex]
Initial value: 250
Decay
Decay rate: 11%
[tex] y = 4 0 ( 1.11 ) ^ x [/tex]
Initial value: 40
Growth
Growth rate: 11%
Step-by-step explanation:
The function we have on the left of the table is:
[tex] y = 2 5 0 ( 0 . 8 9 ) ^ x [/tex]
Initial value (when x = 0): [tex] y = 2 5 0 ( 0 . 8 9 ) ^ 0 [/tex]
y = 250 (initial value)
Growth or Decay: 0.89 < 1 so decay
Decay rate: (1 - 0.89) * 100 = 11%
Function on right side:
[tex] y = 4 0 ( 1.11 ) ^ x [/tex]
Initial value (when x = 0): [tex] y = 4 0 ( 1 . 1 1 ) ^ 0 [/tex]
y = 40 (initial value)
Growth or decay: 1.11 > 1 so growth
Growth rate: (1.11 - 1) * 100 = 11%
i took the test 100%
a construction crew is lengthening a road that originally measured 41 miles. The crew is adding one mile per day. The length, L(in miles), after d dayys of construction is given by following function L(d)=41+d what is the length of the road after 35 days
Answer:
L = 4d + 54
when d = 31 days
L = 4(31) + 54
L = 124 + 54
L = 178 miles
Step-by-step explanation:
The length of the road after 35 days of construction is 76 miles.
Explanation:The length of the road after 35 days can be calculated using the given function L(d) = 41 + d, where L represents the length in miles and d represents the number of days of construction. To find the length after 35 days, we substitute d = 35 into the function.
L(35) = 41 + 35
L(35) = 76
Therefore, the length of the road after 35 days of construction is 76 miles.
Learn more about Lengthening of road here:
https://brainly.com/question/34454511
#SPJ2
ABC is dilated by a scale factor of 0.5 with the origin as the center of dilation resulting in the image ABC. If a equals (2, 2), b equals (4, 3), and c equals (6, 3), what is the length of BC?
Answer:
BC should be 1 unit
Step-by-step explanation:
Answer:
1 unit is your answer
the cost of a service call to fix a washing machine can be expressed by the linear function y = 45x + 35, where y represents the total cost and x represents the number of hours it takes to fix the machine. what does the y-intercept represent?
The y-intercept is where it crosses the y-axis. That means the x-coordinate is zero there. So this point represents how much it cost before any hours are applied. This is also known as the initial cost.
Write an equation in point-slope form for the line through the given point that has the given slope (-2,-7);m=-3/2
For this case we have that the point-slope equation of a line is given by:
[tex](y-y_ {0}) = m (x-x_ {0})[/tex]
Where:
m: It's the slope
[tex](x_ {0}, y_ {0}):[/tex] It is a point
We have as data that:
[tex](x_ {0}, y_ {0}): (- 2, -7)\\m = - \frac {3} {2}[/tex]
We replace:
[tex](y - (- 7)) = - \frac {3} {2} (x - (- 2))\\(y + 7) = - \frac {3} {2} (x + 2)[/tex]
Answer:[tex](y + 7) = - \frac {3} {2} (x + 2)[/tex]
(06.02 mc) the equation of line cd is y=3x-3. Write an equation of a line perpendicular to line cd in slope intercept form that contains points 3,1
Answer:
y = - [tex]\frac{1}{3}[/tex] x + 2
Step-by-step explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
y = 3x - 3 ← is in slope- intercept form
with slope m = 3
Given a line with slope m then the slope of a line perpendicular to it is
[tex]m_{perpendicular}[/tex] = - [tex]\frac{1}{m}[/tex] = - [tex]\frac{1}{3}[/tex], hence
y = - [tex]\frac{1}{3}[/tex] x + c ← is the partial equation of the perpendicular line
To find c substitute (3, 1) into the partial equation
1 = - 1 + c ⇒ c = 1 + 1 = 2
y = - [tex]\frac{1}{3}[/tex] x + 2 ← equation of perpendicular line
Answer:
y = -1/3x + 2
got it correct on my test
A home’s value increases at an average rate of 5.5% each year. The current value is $120,000. What function can be used to find the value of the home after x years?
Answer:
Step-by-step explanation:
To build the equation we need to get the value.
120,000
Lets add the percent which is 1.055 since it is 5.5% added to nothing increasing
120,000(1.055)x
Answer:
120000(1.055)x
Step-by-step explanation
what is the greatest common factor of the following monomials: 12g^5h^4 g^5h^2
Answer:
g^5h^2
Step-by-step explanation:
12g^5h^4, g^5h^2
This is one way of doing it. Break down every number and every variable into a product of the simplest factors. Then see how many of each factor appear in both monomials.
12g^5h^4 = 2 * 2 * 3 * g * g * g * g * g * h * h * h * h
g^5h^2 = g * g * g * g * g * h * h
So far you see every single prime factor of each monomial.
Now I will mark the ones that are present in both. Those are the common factors.
12g^5h^4 = 2 * 2 * 3 * g * g * g * g * g * h * h * h * h
g^5h^2 = g * g * g * g * g * h * h
The greatest common factor is the product of all the factors that appear in both monomials.
GCF = g * g * g * g * g * h * h = g^5h^2
What is the solution to the equation
Answer:
x = -13
Step-by-step explanation:
Distribute:
8 - 6x + 10x - 15 = 20 - 5x
Combine like terms:
4x - 7 = 20 - 5x
Isolate Variable
-x = 13
-1(-x) = -1(13)
x = -13
Answer: [tex]x=3[/tex]
Step-by-step explanation:
You need to apply Distributive property on the left side of the equation:
[tex]2(4-3x)+5(2x-3)=20-5x\\\\8-6x+10x-15=20-5x[/tex]
Now you must add the like terms on the left side of the equation:
[tex]-7+4x=20-5x[/tex]
Add [tex]5x[/tex] to both sides:
[tex]-7+4x+5x=20-5x+5x\\\\-7+9x=20[/tex]
Add 7 to boht sides of the equation:
[tex]-7+9x+7=20+7\\\\9x=27[/tex]
And finally, divide both sides by 9:
[tex]\frac{9x}{9}=\frac{27}{9}\\\\x=3[/tex]
HELP!!! THANK YOU SM
ACCURATE ANSWERS PLEASE
Answer: C
Step-by-step explanation:
1 + 2sin(x+pi)
1 is adding to the y, so it is a vertical shift of 1 unit,
2 is a stretch because it is multiplying to the sin,
and pi is adding to the x, so it is a phase shift.
Kinsley's age is 7 years less than twice Jacobs age if kensley is 13 years old how old is Jacob
Answer:
Age of Jacob is 10 years.
Step-by-step explanation:
Let the age of Jacob = x years and age of Kinsley = y years
Then by first statement " Kinsley's age is 7 years less than twice of Jacob's age"
y = 2x - 7
By second statement " Kensley is 13 years old "
y = 3 years
By putting y = 13 years in the equation
13 = 2x - 7
2x = 13 + 7
2x = 20
x = [tex]\frac{20}{2}[/tex] = 10 years
Therefore, age of Jacob is 10 years.
Answer:
The Answer is B. 10
Hope This Helps!
6x^3+(-3x^3y^2) when simplified is
Answer:
6x^3-3x^3y^2
Step-by-step explanation:
6x^3+\left(-3x^3y^2\right)
6x^3+\left(-3x^3y^2\right)=6x^3-3x^3y^2
=6x^3-3x^3y^2
the answer is 3x^3(2-y^2).
6x^3 + (-3x^3y^2) =
6x^3 - 3x^3y^2 =
3x^3(2-y^2)
find the difference. 60 degrees-30 degrees, 50'-40', 40"-50"
Answer:
60 degrees-30 = 90
50'-40'= 10
40"-50"= 10
Please mark brainliest and have a great day!
Which is a true statement comparing the graphs of x^2/6^2-Y^2/8^2 = 1 and x^2/8^2-y^2/6^2 = 1?
The foci of both graphs are the same points.
The lengths of both transverse axes are the same.
The directrices of = 1 are horizontal while the directrices of = 1 are vertical.
The vertices of = 1 are on the y-axis while the vertices of = 1 are on the x-axis.
Answer:A
Step-by-step explanation:
Edge 21’
The true statement comparing the graphs of x^2/6^2-Y^2/8^2 = 1 and x^2/8^2-y^2/6^2 = 1 is: The foci of both graphs are the same points.
True statement comparing the graphsWhen we look at graphs of x^2/6^2-Y^2/8^2 = 1 and x^2/8^2-y^2/6^2 = 1 we would tend to see that the focus or foci of this two graph are the same point.
In order to know or determine that both graph are the same point or in order to determine each conic you have to focus on where the point crosses the axes.
Therefore the true statement comparing the graphs of x^2/6^2-Y^2/8^2 = 1 and x^2/8^2-y^2/6^2 = 1 is: The foci of both graphs are the same points.
Learn more about True statement comparing the graphs here: https://brainly.com/question/24249361
#SPJ2
What does x equal?
angle2 = (20x - 1), and angle3 = (4x + 13)
Answer:
x = 7
Step-by-step explanation:
angles 2 and 3 form a straight angle and are supplementary, that is they sum to 180°, hence
∠2 + ∠3 = 180 ← substitute values
20x - 1 +4x + 13 = 180
24x + 12 = 180 ( subtract 12 from both sides )
24x = 168 ( divide both sides by 24 )
x = 7
Evaluate a + 7b if a = 14 and b =12
Plug 14 in for a and 12 in for b like so...
14 + 7(12)
14 + 84
98
Hope this helped!
~Just a girl in love with Shawn Mendes
The equation of a linear function in point-slope form is y – y1 = m(x – x1). Harold correctly wrote the equation y = 3(x – 7) using a point and the slope. Which point did Harold use? When Harold wrote his equation, the point he used was (7, 3). When Harold wrote his equation, the point he used was (0, 7). When Harold wrote his equation, the point he used was (7, 0). When Harold wrote his equation, the point he used was (3, 7).
For this case we must find the point that Harold used to arrive at the following equation:
[tex]y = 3 (x-7)[/tex]
Starting from the fact that the equation of the point-slope form of a line is given by:
[tex](y-y_ {1}) = m (x-x_ {1})[/tex]
If we compare the standard equation with Harold's, we see that the slope of the line is [tex]m = 3.[/tex]
In addition, it is observed that [tex]x_ {1} = 7[/tex]and [tex]y_ {1} = 0.[/tex]
Then, the correct option is: Harold used the point (7,0)
ANswer:
When Harold wrote his equation, the point was used (7,0).
A point has coordinates (-3,-3). Where is it located in the coordinate plane?
C quadrant 3 because negative x value and negative y value
need help little time left
bAnswer:
B)
Step-by-step explanation: